# `lim_(t->0) (sqrt(1 + t) - sqrt(1 - t))/t` Evaluate the limit, if it exists.

*print*Print*list*Cite

### 2 Answers

`lim_(t->0) (sqrt(1 + t) - sqrt(1 - t))/t`

sol:

`lim_(t->0) (sqrt(1 + t) - sqrt(1 - t))/t` ---------------------(1)

Taking the numerator we get

`sqrt(1 + t) - sqrt(1 - t)`

`= (sqrt(1 + t) - sqrt(1 - t)) *((sqrt(1 + t) + sqrt(1 - t))/(sqrt(1 + t) + sqrt(1 - t)))`

`= ((sqrt(1 + t))^2 - (sqrt(1 - t))^2)/(sqrt(1 + t) + sqrt(1 - t))`

`= 2t//(sqrt(1 + t) + sqrt(1 - t))`

now taking the (1) we get

`lim_(t->0) (sqrt(1 + t) - sqrt(1 - t))/t`

=`lim_(t->0) (2t/(sqrt(1 + t) + sqrt(1 - t)))/t`

= `lim_(t->0) (2/(sqrt(1 + t) + sqrt(1 - t)))`

now as ` t->0` we get

= `(2/(sqrt(1 + 0) + sqrt(1 - 0)))`

=`2/(1+1)`

= `2/2 = 1`

is the soultion

Plugging in t = 0 into the function results in the indeterminate form 0/0. We could multiply by conjugates and simplify the expression. However, since the numerator and denominator are both differentiable functions, we can apply L'Hopital's rule, which will be easier. Take the derivative of the numerator and denominator.

`lim_(t->0) ( .5(1 + t)^(-1/2) + .5(1 - t)^(-1/2) )/(1)` Plugging in t = 0 shows that the limit is 1.

**Sources:**